2019
DOI: 10.33024/hjk.v13i3.1665
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran kecemasan narapidana wanita di Sumatera Barat

Abstract: Anxiety levels among female inmates in west Sumatra-IndonesiaBackground: Life in prison causes inmates to experience psychological problems. Some psychological problems that are often encountered in prisoners with the highest symptoms are stress, anxiety, aggressive behavior, and psychosomatic. An anxiety problem is found to be higher than other psychological problems that occur in female prisoners.Purpose: Knowing of description of anxiety levels among female prisoners in West Sumatra-Indonesia.Methods: The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
1
0
2
Order By: Relevance
“…The results showed that most female prisoners had senior high school education levels. The results of this study are supported by previous research which shows that most of the prisoners have senior high school education (58.8%) (Mandira et al, 2019). The education level of female prisoners will affect the level of their understanding so that it helps them to understand the information obtained and use it as an alternative problem solving so as to form an adaptive coping mechanism in overcoming various problems in prison such as anxiety, feelings of guilt and regret, disappointment with family attitudes, and feeling that life is not meaningful (Hayati, 2015;Mutoharoh, 2009;Putri, Ira, & Hilma, 2014).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed that most female prisoners had senior high school education levels. The results of this study are supported by previous research which shows that most of the prisoners have senior high school education (58.8%) (Mandira et al, 2019). The education level of female prisoners will affect the level of their understanding so that it helps them to understand the information obtained and use it as an alternative problem solving so as to form an adaptive coping mechanism in overcoming various problems in prison such as anxiety, feelings of guilt and regret, disappointment with family attitudes, and feeling that life is not meaningful (Hayati, 2015;Mutoharoh, 2009;Putri, Ira, & Hilma, 2014).…”
Section: Resultssupporting
confidence: 89%
“…Most of the female prisoners who were in prison had moderate levels of anxiety. The results of this study are supported by research conducted by Mandira which shows that female prisoners experience anxiety in the moderate category of 53.8% (Mandira et al, 2019). These results indicate that female prisoners are not only feeling anxiety before the time of release Prison conditions play an important role in prisoners' anxiety because prisoners have to adapt to new places and roles (Vaerøy, 2011).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Pengalaman bahwa komunikasi demikian dimungkinkan akan membawa dampak positif dalam kehidupan dengan orang-orang yang dekat di kemudian hari. Bagi konselor, konseling kelompok dapat bermanfaat sekali karena melalui interaksi dengan anggota-anggota kelompok, mereka akan mengembangkan berbagai keterampilan yang pada intinya meningkatkan kepercayaan diri dan kepercayaan terhadap orang lain serta menurunkan kecemasan (Mandira et al, 2019).…”
Section: Pendahuluanunclassified
“…. Beberapa masalah kesehatan mental yang sering terjadi pada WBP yaitu stres, cemas, perilaku agresif, dan psikosomatis (Mandira et al, 2019). Masalah kesehatan mental yang tinggi diderita WBP perempuan yaitu depresi (Affizal & Mazlan, 2014).…”
unclassified